Dynamic B0 shimming of the human brain at 9.4 T with a 16‐channel multi‐coil shim setup. Issue 4 (9th February 2018) - Aghaeifar, Ali; Mirkes, Christian; Bause, Jonas; Steffen, Theodor; Avdievitch, Nikolai; Henning, Anke; Scheffler, Klaus
Abstract : Purpose: A 16‐channel multi‐coil shimming setup was developed to mitigate severe B0 field perturbations at ultrahigh field and improve data quality for human brain imaging and spectroscopy. Methods: The shimming setup consisted of 16 circular B0 coils that were positioned symmetrically on a cylinder with a diameter of 370 mm. The latter was large enough to house a shielded 18/32‐channel RF transceiver array. The shim performance was assessed via simulations and phantom as well as in vivo measurements at 9.4 T. The global and dynamic shimming performance of the multi‐coil setup was compared with the built‐in scanner shim system for EPI and single voxel spectroscopy. Results: The presence of the multi‐coil shim did not influence the performance of the RF coil. The performance of the proposed setup was similar to a full third‐order spherical harmonic shim system in the case of global static and dynamic slice‐wise shimming. Dynamic slice‐wise shimming with the multi‐coil setup outperformed global static shimming with the scanner's second‐order spherical‐harmonic shim. The multi‐coil setup allowed mitigating geometric distortions for EPI. The combination of the multi‐coil shim setup with the zeroth and first‐order shim of the scanner further reduced the standard deviation of the B0 field in the brain by 12% compared with the case in which multi‐coil was used exclusively. Conclusion: The combination of a multi‐coil setup and the linear shim channels of the scanner provides a straightforward solution for implementing dynamic slice‐wise shimming without requiring an additional pre‐emphasis setup.